Health Education on Cervical Cancer and IVA Test in Depok City in 2024 - Novelia, Shinta; Andi Maya Sari Usman; Nabila (International Journal of Community Services, 2025)
Cervical cancer is the second most common cancer experienced by women in Indonesia after breast cancer. About 36,000 new cases of cervical cancer are diagnosed each year. Most cases of cervical cancer are caused by an infection with the Human Papillomavirus (HPV), which is transmitted through sexual intercourse. There is an HPV vaccine that can prevent this infection and reduce the risk of cervical cancer. Although Pap smear screenings are available, the participation rate in screening remains low. Only about 10% of women in Indonesia undergo Pap smear examinations regularly. Symptoms of cervical cancer often do not appear until the advanced stages. Frequently overlooked symptoms include abnormal bleeding, pelvic pain, and unusual vaginal discharge. There is still a need to increase public awareness about the importance of preventing and detecting cervical cancer early. Health education programs and HPV vaccination are expected to reduce the incidence and mortality of cervical cancer. In Depok City, data from the Depok City Government published on the Official News Portal in April 2023 indicate that the number of cervical cancer cases increased from 69 cases in 2021 to 179 cases in 2022. Therefore, it is necessary to carry out health education and early detection of cervical cancer, such as the IVA Test, for women of reproductive age. By increasing public knowledge about cervical cancer and the importance of early detection, it is hoped that the incidence of cervical cancer will decrease in Depok City. The activity was carried out for 8 women. The results found that the majority of the women did not know well about cervical cancer and the IVA Test. IVA test results were found normal among all women. This activity is very helpful to educate women about cervical cancer to prevent it.